Public mental health - a challenge for local communities and research: editorial - Priebe, Stefan; Reininghaus, Ulrich (Psychological medicine, 2024)
Common approaches for improving the mental health of the population in general and of vulnerable groups in particular include policies to address social determinants and the expansion of professional health services. Both approaches have substantial limitations in practice. A more promising option is actions that utilize resources that either already exist or can easily be generated in local communities. Examples are provided for various local initiatives with the potential to facilitate helpful interactions and relationships that are likely to benefit the mental health of significant parts of the population. Developing and implementing such initiatives is a challenge to communities, while their evaluation may require innovative methods in research.
Erstmals online veröffentlicht: 10. September 2024
Gesehen am 27.01.2024